Horizontal Bone Augmentation with Simultaneous Implant Placement in the Aesthetic Region: A Case Report and Review of the Current Evidence - Izzetti Rossana; Cinquni Chiara; Alfonsi Fortunato; Nisi Marco; Covelli Michele; Garcia Mira Berta; Priami Mattia; Barone Antonio (Medicina)
This study aimed to describe a case of simultaneous guided bone regeneration (GBR) and implant placement in a patient with prior aesthetic implant failure, focusing on achieving optimal aesthetic and functional outcomes, and to perform a literature review of the current evidence. A 38-year-old male presented with an improperly positioned implant at the level of the right upper central (tooth 2.1), leading to aesthetic and functional issues. The initial assessment included a panoramic radiograph revealing marginal bone loss and an enlarged peri-implant space, necessitating implant removal. Following implant removal and provisional restoration, the patient was re-evaluated for subsequent therapeutic treatments. The patient underwent orthodontic treatment to improve mesio-distal spacing, followed by surgical intervention involving GBR and simultaneous implant placement. The GBR procedure utilised bone substitutes and resorbable membranes, with soft tissue augmentation conducted subsequently. The surgical intervention involved local anaesthesia, flap design, defect assessment, and palatally oriented implant placement. GBR was then performed. After six months, implant uncovering and soft tissue augmentation were conducted. The implant was loaded with a screwed restoration following complete hard and soft tissue healing. The patient was monitored every six months for two years, then annually. At the 10-year follow-up, no signs of bone resorption or soft tissue inflammation were observed. This case demonstrated that GBR and simultaneous implant placement, with the application of advanced biomaterials, effectively promoted osseointegration and maintained aesthetic and functional stability over a decade.